Inpatients’ experience and the associated factors: A cross-sectional study at Lung hospital, Son La, in 2020 - Nguyen Huu, Thang; Doan Thi Nguyet, Minh; Tran Thanh, Huong; Pham Hai, Thanh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objectives: Medical facilities with an autonomous tendency always try to serve positive and pleasant experiences to improve the brand name, increase patient satisfaction and loyalty. A descriptive cross-sectional study was conducted on 245 inpatients at Lung Hospital in Son La province in 2020. To describe the current situation of the inpatient's experience at Lung Hospital in Son La province by 2020 and its related factors.Methods: This was a cross-sectional study conducted on 245 inpatients at Son La Lung HospitalResults: The study showed that the total score of inpatients’ experience ranged from 22 points to 57 points and the mean of it was 39.7 (6.13) points. Subject's experience scores were divided into 2 groups, the satisfied group accounted for 32.7% and the percentage of the unsatisfied group was 67.3%. As compared to men, a higher total score of women was (OR: 1.134; 95% CI: 0.284-0.997).  The urban area group’s score was 1,190 times higher than that of those who live in rural and mountainous areas (95% CI: 1,010 - 1,400). The middle-income group had more positive experience than the low-income group (OR: 1.180; 95% CI: 1.010 - 1.370).Conclusions: Our research showed that gender, living area and economic condition affected the total score of inpatients’ experience at the Lung hospital.
Keywords: Patient experiences; inpatient treatment; hospital; associated factors